Investigation on the relationship of dimensions of the maxillary sinus drainage system with the presence of sinusopathies: a cone beam computed tomography study - de Carvalho, Ana Beatriz Gomes [UNESP]; Costa, André Luiz Ferreira; Fuziy, Acácio; de Assis, Afonso Celso Souza [UNESP]; Castro Veloso, José Ribamar; Coutinho Manhães, Luiz Roberto [UNESP]; Santamaria, Mauro Pedrine [UNESP]; de Castro Lopes, Sérgio Lucio Pereira [UNESP] (Elsevier, 2018)
Objective: This study sought to assess the relationship between the dimensions of the maxillary sinus drainage system with the content of sinuses. Design: Three-hundred cone beam computed tomography images were selected from a database (105 males and 195 females). The images were assessed by a single investigator, trained and calibrated, performing image analysis. The length of the infundibulum and the ostium height in both maxillary sinuses were measured. The data were analyzed using Minitab 1, using 5% as a critical p-value. Results: A significant gender difference was also found for presence in the normal content of sinus for females and presence of antral pseudocyst for males (p < 0.05). Subjects with normal content in the maxillary sinus present lower ostium height values. There were statistically significant with presence of and higher ostium height values and antral pseudocyst (p < 0.01). Conclusion: The current study results demonstrated that some sinusopathies were significantly related to dimensions of maxillary sinus drainage.
Keywords: Anatomy; Diagnostic imaging; Paranasal sinus